Life and death metaphors in some short stories by Jack London from cognitive perspective = Ẩn dụ về sống và chết trong một số truyện ngắn của Jack London dưới góc nhìn tri nhận. M.A Thesis Linguistics: 60 22 15 - Hoàng, Diệu Thu (University of Languages and International Studies, 2017)
43 p. + CD-ROM